Geoprocessamento aplicado na determinação das subclasses de capacidade de uso do solo para o planejamento conservacionista - Da Silveira, Gabriel Rondina Pupo [UNESP]; Campos, Sérgio [UNESP]; Garcia, Yara Manfrin [UNESP]; Silva, Hugo Amancio Sales [UNESP]; De Campos, Mariana [UNESP]; Nardini, Rafael Calore [UNESP]; Felipe, Andrea Cardador [UNESP] (My University, 2013)
This work aimed at the determination of the subclasses of capacity of soil use of the Stream São Caetano watershed - Botucatu, São Paulo, seeking the planning of practices of conservation of the soil in the area through System of Geographical Information Idrisi Selva. The study area is located among the geographical coordinates: 48° 26' 25 W, 48° 29' 27 W, 22° 46' 21 S and 22° 52' 32 S, presenting an area of 3316.95ha. The capacity chart of soil use of the basin was obtained starting from the crossing of the letters of steepness and of soils with the table of judgment of the capacity classes of soil use and of the constant recommendations in the utilitarian rising of the physical middle and classification of the lands in the system of use capacity. The results allowed to infer that the subclasses IIIs,e, IVs and VIe are constituted in more than 70% of the area and for almost 100% of the units of soils Latossolo Vermelho distrófico and Neossolo Eutrophico litólico. GIS-IDRISI allowed quickly through their modules the discrimination, the mapping and the quantification of the areas of the subclasses of capacity of soil use of the watershed.
Geoprocessing applied for determination of the subclasses soil use capacity for conservationist planning
Keywords: Geographical Information System; Slope classes; Soil units